Attitudes and Perceptions of Agricultural Water Use in Florida Expressed by the General Public and Local Officials - Courtney T. Owens; Alexa J. Lamm; Ricky W. Telg (EDIS)
The use of water has become increasingly contentious because an increased population is sharing a decreasing amount of water. Water remains Florida’s most plentiful natural resource but is at risk as the agriculture industry and Floridians demand more water for a variety of uses. This 4-page fact sheet discusses the media’s influence on perceptions of agricultural water use, the measurement of attitudes and perception towards agricultural water use, and ways to educate the general public and local officials on this issue. Written by Courtney T. Owens, Alexa J. Lamm, and Ricky W. Telg, and published by the Department of Agricultural Education and Communication, April 2016.